2022
DOI: 10.3390/antiox11020418
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of PE with Pomegranate Extract: Contradictions and Possible Mechanisms

Abstract: Dry pomegranate peel was extracted with acetone and the extract was added to a Phillips type polyethylene. The concentration of the extract was changed from 0 to 1000 ppm in six steps and stabilization efficiency was checked by the multiple extrusion of the polymer followed by the characterization of chemical structure, processing, and residual stability. The results confirmed the excellent processing stabilization efficiency of the extract, but also the poor long-term stability of PE containing it in accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Unfortunately, the extracts have a very moderate stabilization effect; their OIT value hardly exceeds 10 min. The phenomenon has been observed before; the extract of pomegranate peel had a very good processing stabilization effect but offered no residual stability for the polymer [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Unfortunately, the extracts have a very moderate stabilization effect; their OIT value hardly exceeds 10 min. The phenomenon has been observed before; the extract of pomegranate peel had a very good processing stabilization effect but offered no residual stability for the polymer [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 75%
“…Flavonoids produced by plants, such as quercetin [ 15 , 16 , 17 ], rutin [ 18 ] and dihydromyricetin [ 19 ], proved efficient stabilizers in polyethylene, and the comparison of a natural extract, silymarin, to its main component, silybin, showed that extracts could be more efficient than purified single compounds [ 20 ]. Recently, pomegranate peel extract was used for the processing stabilization of polyethylene, and its efficiency exceeded that of the commercial hindered phenolic antioxidant, Irganox 1010 (I1010) [ 21 , 22 ]. Unfortunately, the residual, long-term stability of the polyethylene containing the extract was quite small; thus, further study is needed to find an optimum solution for the use of this extract.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin [16], dihydromyricetin [17], and rutin [18] provided sufficient melt stability for PE already at 50 ppm, and residual oxidative stability at 250 ppm additive content. Not only the pure compounds but also natural extracts have considerable stabilization efficiency; thus, sooner or later they will find their way into industrial practice [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%